1975
DOI: 10.1007/bf00562321
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of triprolidine and clemastine on histamine antagonism and performance tests in man: Implications for the mechanism of drug induced drowsiness

Abstract: The effects of triprolidine hydrochloride 1.25, 2.5 and 5 mg, clemastine 1 and 2 mg and lactose dummy administered orally, in a balanced order, at weekly intervals to 12 healthy volunteers, on the flare and weal responses to intradermal histamine injection, and also on both subjective effects and objective psychomotor tests were examined. The histamine response was significantly larger at 09.00 h falling through the day but increasing by late afternoon. Triprolidine produced a dose-related antagonism of both f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
3

Year Published

1982
1982
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 7 publications
4
20
3
Order By: Relevance
“…Four injection sites within each row were allocated randomly to the different treatments for each subject. Twenty minutes later, the longest and narrowest orthogonal axes of the resultant wheals and flares were measured using a plastic ruler, and areas calculated assuming an elliptical shape (Peck et al, 1975).…”
Section: Assessment Of Histamine Antagonismmentioning
confidence: 99%
See 1 more Smart Citation
“…Four injection sites within each row were allocated randomly to the different treatments for each subject. Twenty minutes later, the longest and narrowest orthogonal axes of the resultant wheals and flares were measured using a plastic ruler, and areas calculated assuming an elliptical shape (Peck et al, 1975).…”
Section: Assessment Of Histamine Antagonismmentioning
confidence: 99%
“…In this study, the assessment of histamine antagonism was performed 0.75 h after the final CP test. However, previous work has shown such an oral dose to have activity at 1, 2, 3 and 4 h post-drug ingestion using the same test system (Hamilton et al, 1982;Peck et al, 1975).…”
Section: Salivary Flowmentioning
confidence: 99%
“…Studies in healthy man have shown, however, that the peripheral antihistaminic and central sedative effects of such drugs may be poorly correlated and the question arises whether central depressant effects are related to other pharmacological activity (Peck et al, 1975;Levander et al, 1985). Many antihistamines are not specific Hl-receptor antagonists, and modulation of the activity of neurotransmitters other than histamine could be involved in the sedative effects of a particular drug.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental pharmacology and preliminary clinical investigations ebastine appears to be a potent long-acting drug with no apparent sedative properties in the antihistamine dose range (Roberts et al, 1987). Antihistamines have been used for over 30 years but impairment of psychomotor performance, sedation and anticholinergic effects have been associated with most earlier compounds (Peck et al, 1975;Carruthers et al, 1978;Clarke & Nicholson, 1978;Nicholson & Stone, 1982, 1986Paton & Webster, 1985). Antihistamines without sedation or psychmotor impairment constitute an important clinical development.…”
Section: Introductionmentioning
confidence: 99%